The Aesthetics of Music - Scruton, Roger (Oxford Oxford University Press, 1991)
What is music, what is its value, and what does it mean? In this stimulating volume, Roger Scruton offers a comprehensive account of the nature and significance of music from the perspective of modern philosophy. The study begins with the metaphysics of sound. Scruton 7istinguishes sound from tone; analyzes rhythm, melody, and harmony; and explores the various dimensions of musical organization and musical meaning. Taking on various fashionable theories in the philosophy and theory of music, he presents a compelling case for the moral significance of music, its place in our culture, and the need for taste and discrimination in performing and listening to it. Laying down principles for musical analysis and criticism, this bold work concludes with a theory of culture--and a devastating demolition of modern popular music.
Keywords: 20th Century (1901-2000); Music philosophy and esthetics; Conservatism; United Kingdom